The costs and benefits of senotherapeutics for human health - Raffaele, Marco; Vinciguerra, Manlio (The lancet. Healthy longevity, 2022)
Cellular senescence is a major contributor to age-related diseases in humans; however, it also has a beneficial role in physiological and pathological processes, including wound healing, host immunity, and tumour suppression. Reducing the burden of cell senescence in animal models of cardiometabolic disorders, inflammatory conditions, neurodegenerative diseases, and cancer using pharmaceutical approaches that selectively target senescent cells (ie, senolytics) or that suppress senescence-associated secretory phenotype (ie, senomorphics) holds great promise for the management of chronic age-associated conditions. Although studies have provided evidence that senolytics or senomorphics are effective at decreasing the number of senescent cells in humans, the short-term and long-term side-effects of these therapies are largely unknown. In this Review, we systematically discuss the senolytics and senomorphics that have been investigated in clinical trials or have been used off-label, presenting their various adverse effects. Despite the potential of senotherapeutics to transform anti-ageing medicine, a cautionary approach regarding unwanted dose-dependent side-effects should be adopted.
Keywords: léky proti stárnutí; nádory; Cellular Senescence; stárnutí; Animals; Humans; lidé; analýza nákladů a výnosů; Cost-Benefit Analysis; zvířata; Senotherapeutics; Aging; stárnutí buněk; Neoplasms